Wuasa Village Financial Management Analysis - Gazali, Moh.; Muslimin; Kasim , Yunus (Journal of Humanities, Community Service, and Empowerment, 2024)
This research aims to determine how the financial management process in Wuasa Village, North Lore District, Poso Regency, is by Minister of Home Affairs Regulation Number 20 of 2018 concerning Village Financial Management from 2021 to 2023. This type of research is descriptive qualitative with primary data, namely direct observation and interviews related to APBdes planning and accountability in Wuasa Village. In contrast, the secondary data used are APBdes reports for 2021, 2022, and 2023. This research uses data analysis techniques by collecting, grouping, and analyzing data so that Conclusions are drawn regarding the research objectives to be achieved. This research shows that the village fund management system, from planning to accountability, carried out by the Wuasa Village government, is governed by applicable regulations both technically and administratively. However, the amount of village funds received tends to decrease every year. This is caused by several factors: The poor population has decreased, and the status of the village has improved.